Co-designing complex interventions with people living with dementia and their supporters. (February 2022) - Lord, Kathryn; Kelleher, Daniel; Ogden, Margaret; Mason, Clare; Rapaport, Penny; Burton, Alexandra; Leverton, Monica; Downs, Murna; Souris, Helen; Jackson, Joy; Lang, Iain; Manthorpe, Jill; et al.
Background and objectives: We engaged people living with dementia, family carers and health and social care professionals in co-designing two dementia care interventions: for family carers and people living with dementia (New Interventions for Independence in Dementia Study (NIDUS)-family and home-care workers (NIDUS-professional training programme). Research design and methods: Over October 2019–March 2020, we invited public and patient (PPI) and professional members of our NIDUS co-design groups to complete the PPI Engagement Evaluation Tool (designed to assess engagement activities), and non-professional PPI members to participate in qualitative telephone interviews. We thematically analysed and integrated mixed-methods findings. Results: Most (15/20; 75%) of the PPI members approached participated. We identified four themes: (1) Creating the right atmosphere: participants found group meetings positive and enabling, though one health professional was unsure how to position themselves within them; (2) Participants influencing the outcome: while most members felt that they had some influence, for one carer consultation seemed too late to influence; (3) Having the right information: several carers wanted greater clarity and more regular updates from researchers; (4) Unique challenges for people living with dementia: memory problems presented challenges in engaging with substantial information, and within a large group. Discussion and implications: We reflect on the importance of providing accessible, regular updates, managing power imbalances between co-design group members with lived and professional experiences; and ensuring needs and voices of people living with dementia are prioritised. We encourage future studies to incorporate evaluations of co-design processes into study design.